Creative Writing 601 Special Edition Preface - Wilson, Jani (Te Kaharoa, 2019)
Creative Writing 601 (soon-to-be-hopefully-renamed) is based in Te Ara Poutama, under the auspices of the Māori Media degree, the only degree of its kind in the world. To fuel, perhaps, an unknown/untapped desire for creative writing, potentially publishing in Te Kaharoa is an opportunity for our year one and two tauira to experience the publication process from conceptualisation and development in the classroom, and sending them out into the world. Excited by the prospect of this, we invited a number of our past tauira to submit work to Te Kaharoa as a means of seeing publication through, and potentially setting a pathway for future tauira to follow. Welcome to this experiment.